A Metal-Organic Framework (MOF) Fenton Nanoagent-Enabled Nanocatalytic Cancer Therapy in Synergy with Autophagy Inhibition - Yang, Bowen (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.